Set apart : holy habits of prophets and kings : a Bible study on 1 and 2 Kings : leader guide - LaGrone, Jessica; Youngman, Jenny (Nashville : Abingdon Press, 2015)
Holy Habits of Prophets and Kings.
Cover; Title; Copyright; Contents; Introduction; Leader Helps; Week 1: Solomon; Set Apart by Being Consecrated; Week 2: Elijah; Set Apart by Listening; Week 3: Elijah and Elisha; Set Apart by Mentoring; Week 4: Elisha and Naaman; Set Apart by Practicing Humility; Week 5: Hezekiah; Set Apart by Worshiping God; Week 6: Josiah; Set Apart by Discovering God's Word; Group Roster
Vendor-supplied metadata.
Keywords: Bible. -- Study and teaching; Christian education of adults; RELIGION / Biblical Studies / Old Testament; Electronic books; Electronic books